1994
DOI: 10.1111/j.1365-2109.1994.tb00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of mixed feeding schedules in fish culture: field trials on catla, Catla catla (Hamilton-Buchanan), rohu, Labeo rohita (Hamilton), and common carp, Cyprinus carpio L.

Abstract: Abstract. The applicability of mixed feeding schedules using low‐and high‐protein diets was evaluated by three on‐farm field trials conducted in fertilized earthen ponds. Rohu, Labeo rohita (Hamilton), and common carp, Cyprinus carpio L., were used in the first two trials, and catla. Catla catla (Hamilton‐Buchanan), was also included in the third trial. The concept of a mixed feeding schedule was tested using a 1:1 rice bran‐groundnut meal cake mixture, a commonly used feed in Indian carp culture. In a mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Reducing the level of dietary protein to the minimum required level for fish is critical in commercial aquaculture, since excess portion of dietary protein is not only wasted as ammonia via gills, as far as fish growth is concerned, but it is also environmentally destructive (Sugiura and Hardy 2000). It was reported that mixed feeding schedules using diets containing low-and high-protein as in the present study provided an increased and decreased N retention and loss, respectively, in tilapia and carps (De Silva 1985, Nandeesha et al 1993, 1994, 1995, Ali et al 2005. In the presently reported study, the schedules used (1A/1B, 1A/2B and 1A/3B) were in conformity with the above findings to a certain degree but these were not significantly different from the high-protein control diet.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reducing the level of dietary protein to the minimum required level for fish is critical in commercial aquaculture, since excess portion of dietary protein is not only wasted as ammonia via gills, as far as fish growth is concerned, but it is also environmentally destructive (Sugiura and Hardy 2000). It was reported that mixed feeding schedules using diets containing low-and high-protein as in the present study provided an increased and decreased N retention and loss, respectively, in tilapia and carps (De Silva 1985, Nandeesha et al 1993, 1994, 1995, Ali et al 2005. In the presently reported study, the schedules used (1A/1B, 1A/2B and 1A/3B) were in conformity with the above findings to a certain degree but these were not significantly different from the high-protein control diet.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, common carp maintained on the 1A/3B schedule was found to grow well (Srikanth et al 1989). Nandeesha et al (1994) fed Indian major carps with rice bran (low-protein diet) and a mixture of rice-bran-groundnut meal cake (high-protein diet) using mixed feeding schedules and found that fish reared on the 1A/3B schedule performed comparable growth with those fed continuously high-protein diet. Thus, it can be considered that this schedule is promising for rainbow trout as well.…”
Section: Discussionmentioning
confidence: 99%
“…The protein (38%) and iron component of LPF promoted growth significantly, when compared with other test feeds. Nandeesha et al (1994) also reported that mixed diet treatments were superior to single high protein diet because nitrogen retention was higher in the fish fed with mixed treatment. The poor growth rate observed in fish fed with pelleted feed suggests that pellets are not suitable to juvenile Colisa fasciata.…”
Section: Discussionmentioning
confidence: 95%
“…Algae contribute to an increase in protein assimilation and feed utilization [16]. It has been reported that supplementation of Spirulina resulted in increased food utilization, protein efficiency ratio, carcass quality and growth of cultured organisms [40][41][42][43]. Baker's yeast also offers promising possibilities as a substitute for algal live feeds in aquaculture.…”
Section: Discussionmentioning
confidence: 99%